An ageing generation of workers in the labour market - Urbaniak, Bogusława (Problemy społeczne: Trwałość i zmienność w dynamicznej rzeczywistości. Księga jubileuszowa z okazji 45-lecia pracy naukowej i dydaktycznej Profesor Jolanty Grotowskiej-Leder, 2022)
The ageing of the labour force means that an increasing proportion of it is made up of people belonging to the group of older workers. In Poland, the share of people aged 45–64 among the total aged 15–64 was 39,1% in 2019. Due to shrinking labour resources, there is increasing talk of the need to postpone the end of working life age even to 75 in some EU27 countries. The type of labour force participation at older ages and the place of older workers in a polarised labour market remains an open question. The aim of this paper is to present the determinants of the increase in employment of older people mainly by referring to the polarisation of the labour market, the development of entrepreneurship among older people and the scale of discrimination against older people at work and in the labour market. The article uses publicly available data from national and international statistics.